Learning Management Guidelines to Enhance Creative Problem Solving of Pre-Service Teachers - Wisetsat, Channarong; Wisetsat, Wasanathai (Journal of Community Development Research (Humanities and Social Sciences); Vol 13 No 1 (2020): January - March 2020, 2020)
This research aimed to study learning management guideline to enhance creative problem solving of pre-service teachers. There were two phases of the study. First, the researcher analyzed the related documents: researches, books and five Specialists. Research instruments were component synthesis form and suitability assessment form. Second, the fieldwork was applied for authentic study: three academics were Chulalongkorn University, Suan Sunandha Rajabhat University, and Lamplaimat Pattana School. Research instruments were teaching activities, observation form, interview form, relations analysis form and suitability assessment form. The results showed that: The components for creative problem solving of pre-service teachers consisted of five components; (1) fact finding, (2) problem finding, (3) idea finding, (4) solution finding and (5) acceptance finding. The syntax of teaching to enhance creative problem solving of pre-service teachers had five steps; Step 1: study information to enhance fact finding, Step 2: problem identification to enhance problem finding, Step 3: generate ideas to enhance idea finding, Step 4: choose the right idea to enhance solution finding and Step 5: implement to enhance acceptance finding. Keywords: Problem Solving Skills, Learning Management, Pre-Service Teachers